Growth assessment of various formulae of essential minerals and trace elements on whiteleg shrimp at different salinities - Viet Do, Phuong; Thao Nguyen, Suong; Tai Chau, Tao; Nguyen TK, Loan; Touchet, Audric; Gutter, Gaetan; Mahl, Philippe; Phan, Hoang (Vietnam Journal of Biotechnology, 2022)
Whiteleg shrimp (Litopenaeus vannamei) is now the main species cultivated in various geographic locations. Whiteleg shrimp have a wide range of salinity tolerance, but a matter of deficiency of minerals and trace elements need to be taken care of when shrimp are grown in low saline area. It may induce higher mortality and slower growth performances of shrimp. Two stages of shrimp juveniles were subsequently tested with different formulae of a liquid nutraceutical of essential minerals and trace elements. Each stage was performed in a 28-day trial with follow-up parameters of shrimp growth indices and environmental changes throughout the tests. The use of mineral supplementation in whiteleg shrimp diet in low salinity area significantly increased growth performance, survival rate and color intensity. This study has demonstrated the efficacy of a liquid form of mineral supplement product administered by top-coating onto the feed to shrimp during 4 weeks of grow-out at 5‰ salinity, but the application was dependent on formula and dose. Further research on application regime using this liquid mineral product should be performed to optimize a protocol for a whole culture crop as different stages of shrimp may require different supplementation doses.